2018
DOI: 10.5604/01.3001.0012.1310
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Photochromic Spirooxazine/Polyvinylidene Fluoride Fiber Membranes via Electrospinning

Abstract: In this study, photochromic spirooxazine material of N-methyl-3,3-dimethyl-9’-hydroxy-spiro [2H-indole-2-[3H] naphtho [2,1-b] [1,4] oxazine] was synthesised. Spirooxazine/PVDF fiber (SPF) membranes with different contents of spirooxazine were successfully prepared by electrospinning. The SPF membranes were characterised by FTIR and SEM. The photochromic properties and contact angle of the SPF membranes were evaluated. The results show that the SPF membranes change from colorless to blue when exposed to UV ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The peaks at 873 cm À1 and 752 cm À1 were assigned to symmetrical and asymmetrical stretching vibrations of the naphthalene ring. 29,30 By blending SPO with PMMA, the relevant characteristic peaks confirmed that PMMA-SPO fibers had been successfully fabricated. After the PMMA-SPO fiber was irradiated by UV, the peaks representing CQN at 3450 cm À1 and 1632 cm À1 almost disappeared, indicating that PMMA-SPO involved a ringopening reaction.…”
Section: Photochromism Performance Of Pmma-spo Screen Windowmentioning
confidence: 79%
“…The peaks at 873 cm À1 and 752 cm À1 were assigned to symmetrical and asymmetrical stretching vibrations of the naphthalene ring. 29,30 By blending SPO with PMMA, the relevant characteristic peaks confirmed that PMMA-SPO fibers had been successfully fabricated. After the PMMA-SPO fiber was irradiated by UV, the peaks representing CQN at 3450 cm À1 and 1632 cm À1 almost disappeared, indicating that PMMA-SPO involved a ringopening reaction.…”
Section: Photochromism Performance Of Pmma-spo Screen Windowmentioning
confidence: 79%
“…All the above peaks are the characteristic peaks of the wall material polyoxymethylenemelamine; however, no characteristic peaks of spirooxazine photochromic powders are found near 1243, 1081, and 980 cm −1 , indicating that the photochromic powders are coated completely. [ 31 ] For the PVC/photochromic powders composite films, the peaks of 2957, 2929, 1734, and 695 cm −1 mainly come from the contribution of the plasticized PVC film. [ 32 ] The peak around 1549 cm −1 is found in the PVC/photochromic powders composite films, mainly due to the stretching vibration of C═N on the photochromic powders, indicating the existence of photochromic powders in the plasticized PVC composite films.…”
Section: Resultsmentioning
confidence: 99%
“…Moazzenchi synthesized nickel nanoparticles on the surface of polyester fabric using electroless nickel plating, which exhibits ideal conductivity [33,34]. Peng used a laser to process polyester fabric and successfully conducted electroless nickel plating on its surface to research its electrothermal and electromagnetic shielding performance [35][36][37]. However, so far, there have been no attempts to deposit nickel on CFRP via electroless plating as a heater for aircraft deicing.…”
Section: Introductionmentioning
confidence: 99%